Court Operations during the COVID-19 Pandemic - Baldwin, Julie Marie (American journal of criminal justice, 2020)
This paper reviews the distinct nature of the COVID-19 pandemic and examines the resultant court responses and recommendations disseminated by various entities that support courts. Specifically, we contextualize the current environment the present pandemic has created by considering how it compares to the most-recent previous pandemics. We then review guidelines disseminated to the courts and the modifications and innovations implemented by the courts in response to the COVID-19 pandemic. Additional challenges related to these recommendations and modifications are identified and discussed.